Use of inline near‐infrared spectroscopy to predict the viscosity of shampoo using multivariate analysis. (28th June 2019) - Haroon, K.; Arafeh, A.; Martin, P.; Rodgers, T.; Mendoza, Ć.; Baker, M.
Abstract: Objective: In the personal care industry, viscosity is a critical quality attribute that influences product quality and process economics. Like many industrial liquids, personal care liquids are complex non‐Newtonian liquids made up of aqueous surfactant systems whose viscosity depends on the build‐up of micellar networks. Measuring the viscosity of complex liquids offline is easily done using benchtop rheometers and viscometers. The challenge lies in measuring the viscosity of personal care liquids online during manufacturing. Being able to track the viscosity of such products through their manufacturing cycle will not only allow for better process control but also more enhanced quality control. Therefore, the aim of this work was to investigate how proxy measurements using inline near‐infrared (NIR) spectroscopy in transmission mode can be used to predict the viscosity of shampoo. NIR spectroscopy has not, to the best our knowledge, been used to predict the viscosity of complex surfactant systems like shampoo and could significantly affect the way quality is monitored in a manufacturing environment. Method: This work focuses on viscosity changes because of differences in chloride content as salt is often used to adjust viscosity. The relationship between salt content and the viscosity of shampoo is well known following the salt curve. From an industrial perspective the region of interest for the formulation studied in this work only covers a small section of this curve. Therefore, two predictive models were developed: one covering the full range of the salt curve and another focusing on the industrially applicable region. Result: Models were produced using partial least squares (PLS) where both datasets showed some predictive ability with the concentrated region of interest showing enhanced performance [root mean square error of prediction (RMSEP) – 2.32 Pa s] compared with the larger range (RMSEP – 4.44 Pa s). Conclusion: This work provides a good starting point for developing robust predictive models for in situ viscosity measurements for shampoo manufacturing, where further work into different sources of variation and the extent of the modelling capability with regards to different formulations should be studied. Abstract : This work presents a feasibility study into the use of inline near‐infrared spectroscopy to measure the viscosity of shampoo using partial least squares predictive modelling. As salt is commonly used to adjust the viscosity of personal care products, two models were investigated – one covering the whole salt curve and the other being more industrially relevant covering the range expected for shampoo formulations. Both models showed good predictive abilities (RMSEP: 4.44 & 2.32 Pa s respectively) with the concentrated model showing superior performance. Résumé: Objectif: Dans le secteur des soins personnels, la viscosité est une caractéristique de qualité cruciale qui influe sur la qualité du produit et l'économie en matière de processus. Comme de nombreux liquides industriels, les liquides destinés aux soins personnels sont des liquides non newtoniens complexes composés de systèmes tensioactifs aqueux dont la viscosité dépend de l'accumulation de réseaux micellaires. Mesurer la viscosité de liquides complexes hors ligne est facilement effectué à l'aide de rhéomètres et de viscosimètres de paillasse. Le défi consiste à mesurer la viscosité des liquides destinés aux soins personnels en ligne pendant la fabrication. Pouvoir suivre la viscosité de tels produits tout au long de leur cycle de fabrication permettra non seulement de mieux contrôler le processus mais aussi d'obtenir un meilleur contrôle qualité. Par conséquent, l'objectif de ce travail était d'étudier comment des mesures par procuration en utilisant la spectroscopie proche infrarouge (NIR) en ligne en mode de transmission peuvent être utilisées pour prédire la viscosité du shampooing. La spectroscopie proche infrarouge n'a pas, au mieux de nos connaissances, été utilisée pour prédire la viscosité de systèmes tensioactifs comme le shampooing, et elle pourrait significativement affecter la façon dont la qualité est surveillée dans un environnement de fabrication. Méthode: Ce travail se concentre sur les changements au niveau de la viscosité en raison de différences dans la teneur en chlorure puisque le sel est souvent utilisé pour ajuster la viscosité. La relation entre la teneur en sel et la viscosité du shampooing est bien connue suivant la courbe du sel. D'un point de vue industriel, le domaine d'intérêt pour la formulation étudiée dans ce travail couvre seulement une petite section de cette courbe. Par conséquent, deux modèles prédictifs ont été développés : l'un portant sur la gamme complète de la courbe du sel et l'autre se concentrant sur le domaine applicable à l'industrie. Résultat: Les modèles ont été fabriqués en utilisant la méthode des moindres carrés partiels (partial least squares, PLS) où les deux ensembles de données ont montré un certain degré de capacité prédictive, le domaine concentré d'intérêt ayant fait preuve d'une meilleure performance (Root Mean Square Error of Prediction, RMSEP – 2, 32 Pa s) par rapport à la plage de plus grande envergure (RMSEP – 4, 44 Pa s). Conclusion: Ce travail fournit un bon point de départ pour élaborer des modèles prédictifs robustes servant à mesurer la viscosité in situ durant la fabrication des shampooings, mais d'autres travaux portant sur différentes sources de variation et sur l'ampleur de la capacité de modélisation de diverses formules doivent être effectués.